Copper‐Catalyzed Oxidative Coupling of Carboxylic Acids with N, N‐Dialkylformamides: An Approach to the Synthesis of Amides1. Issue 7 (24th January 2013) - Kumar, P. Santhosh; Kumar, G. Sathish; Kumar, R. Arun; Reddy, N. Veera; Rajender Reddy, K.
Abstract: A new synthetic approach for amide bond formation through the oxidative coupling of N, N ‐dialkylformamides with carboxylic acids was achieved by using a copper catalyst. Furthermore, this method was applied in the coupling of chiral amino acids in which the stereochemistry was retained in the resulting amide products. Abstract : A new synthetic approach to amide bond formation through the oxidative coupling of N, N ‐dialkylformamides with carboxylic acids was achieved by using a copper catalyst and aqueous tert ‐butyl hydroperoxide (TBHP) as a sacrificial oxidant. Furthermore, this method was applied in the coupling of chiral amino acids in which the stereochemistry was retained in the resulting amide products.